Antioxidant Properties of Active Fraction Extract Derived from Yellow-Red Pigment Produced by the Marine Sponge-Associated Bacterium Bacillus haikouensis AGS112 and Identification of Related Compounds - Uci Cahlia; Rika Indri Astuti; Jun Nomura; Aris Tri Wahyudi (Bogor Agricultural University, Indonesia, 2023)
Sponge-associated bacteria can produce bioactive compounds similar to the host. Here, the investigation of antioxidant properties of the yellow-red pigment produced by sponge-associated bacterium AGS112 was conducted using in vitro and in vivo analysis. The 16S rRNA gene sequence showed the sponge-associated bacterium AGS112 has the closest similarity with Bacillus haikouensis C-89 (99%). The crude pigment extract produced by Bacillus haikouensis AGS112 contained both phenolic and flavonoid. The peaks occurred at 412 nm and 664 nm, which indicated as the presence of carotenoids and flavonoids, respectively. The active fraction extract obtained through bio-autography TLC, and had more potent antioxidant activity against DPPH (2,2-diphenyl-1-picrylhydrazyl) compared to the crude pigment extract with an IC50 value of 68.62±0.59 µg/ml and 198.88±1.66 µg/ml, respectively. Moreover, the active fraction extract at the concentration of 35 µg/ml could better enhance the viability of Schizosaccharomyces pombe and achieve the highest expression of sod1 and ctt1 genes. Metabolite profiling using LC-MS analysis confirmed the active fraction extract contains eudesmin and artelastin that might be contributed as antioxidants. These results suggest that the active fraction extract of the yellow-red pigment produced by B. haikouensis AGS112 had potency to be used as candidate for natural antioxidants.